MANAGEMENT COMPETENCY RELATIONSHIP TO THE ENTERPRISE PERFORMANCE WITH VARIABLE OF INTERVENING EFFECTIVITY PROJECT TEAM - Zeplin Jiwa Husada Tarigan (Jurnal Teknobisnis, 2012)
Change management system is influenced by the company management competency. because, management determines change through the workings procedures and organization structure. Management competency of companies has positive consequence to effectively project team. The management expertise has ability to decide the people who have talent in order to involve on the project. Project team was formed when a change management system in the form of project. Thus, effectiveness of the project team key user influence on improvement of company performance. Whereas based on a survey by distributing questionnaires and interviews of 42 SMEs (Small and Medium Enterprises) and analyzed with SEM (Structural Equation Modeling) it was found that a positive relationship management competency to change management system. On contrast, it has negative influence between management competence and effectively Project Team. Change management system also affect the effectively project team. Furthermore, enterprise performance was determined by change management system, while effectively project team had no effect at the company as a research object.